Generalised Epidermolysis Bullosa with Severe Anaemia in an Adolescent: A Case Report - Jannawar, Shivam; Ambike, Deepali; Ahmed, Sabahat; Kulkarni, Rajesh K; Ambike, Deepali (Journal of Nepal Paediatric Society, 2021)
EBS is a rare genodermatosis usually inherited in an autosomal dominant fashion, although rare autosomal recessive cases have been reported. In severe generalised EBS, infants exhibit severe symptoms at the onset which tend to improve with time. We report an adolescent with severe generalised epidermolysis bullosa simplex (EBS), the most severe form of EBS, with severe iron deficiency anaemia